2014
DOI: 10.1017/prp.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Among College Youth as a Function of Family SES: The Mediating Effect of Sense of Poverty and the Mitigating Role of Family Resources

Abstract: A lthough college provides an opportunity for socioeconomic advancement, poor college youth confront material scarcity and financial problems and are at risk for psychological distress. Yet, distress is a product not only of poverty per se but of a sense of poverty, or a subjective evaluation of one's socioeconomic conditions vis-à-vis life circumstances. Both sense of poverty and psychological distress, however, can be mitigated by collective problem-solving in the family and by the family's social resources.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Another causal factor that seems to indicate compensatory primary control relates to asking help from others and also giving help to others to cope with their indigence, which is mentioned in the qualitative studies of Filipinos who were born poor (Tuason, 2008). Asking for help to lift one's socio-economic status aligns with discourses related to social networks as a specific form of social resources that poor families use to cope (Hill, Jobling, Pollet, & Nettle, 2014;Reyes & Yujuico, 2014). Again, there seems to be an acknowledgement that one's personal resources are not sufficient to move oneself towards higher social mobility, and help from other people could be recruited for this purpose.…”
Section: Social Mobility Pathways In the Philippinesmentioning
confidence: 99%
“…Another causal factor that seems to indicate compensatory primary control relates to asking help from others and also giving help to others to cope with their indigence, which is mentioned in the qualitative studies of Filipinos who were born poor (Tuason, 2008). Asking for help to lift one's socio-economic status aligns with discourses related to social networks as a specific form of social resources that poor families use to cope (Hill, Jobling, Pollet, & Nettle, 2014;Reyes & Yujuico, 2014). Again, there seems to be an acknowledgement that one's personal resources are not sufficient to move oneself towards higher social mobility, and help from other people could be recruited for this purpose.…”
Section: Social Mobility Pathways In the Philippinesmentioning
confidence: 99%
“…There are currently no published studies that show this relationship with a Filipino sample. One recent study did not actually measure financial stress, but showed that sense of poverty was associated with the experience of psychological distress among students (Reyes & Yujuico, 2014).…”
Section: Financial Stress and Well-being Among Filipino Studentsmentioning
confidence: 99%
“…As the nation slowly progresses toward adopting tuition-free models of financing higher education (Miller-Adams, 2015), this research may help stakeholders to refine support programs for these students. While eliminating tuition financial stressors (Collier et al , 2017), scholarship funding cannot overcome barriers to underrepresented students' success, such as academic preparation, self-efficacy and increased psychological distress (Covarrubias and Fryberg, 2015; Harackiewicz et al , 2014; Reyes and Yujuico, 2014; Soria and Stebleton, 2013). Studying students who receive a tuition benefit provides an opportunity to explore student experiences that do not solely focus on finances and may offer insight to mentoring activities that do not focus on scholarship opportunities.…”
Section: Mentoring and College Student Outcomesmentioning
confidence: 99%